Nutrients and rheumatoid arthritis: From the perspective of neutrophils - Shao, Ya-Ru; Xu, Dan-Yi; Lin, Jin (Frontiers in Immunology, 2023)
Neutrophils are considered as core immune cells involve in the early stage of rheumatoid arthritis (RA) and participate in the disease progression. The underlining mechanisms include the elevated chemotaxis and infiltration of neutrophils, the increase in the reactive oxygen species and the promotion of neutrophil extracellular traps formation. Accumulating studies demonstrated the important role of nutrients intake played in the initiation and progression of RA. This study summarized the effects of several macronutrients and micronutrients on regulating RA through the modulation of activated neutrophils and appealed for a healthy diet in RA-risk individuals as well as RA patients.